Formative Feasting Practices and Virtue Ethics in Deuteronomy$1 (Bs Tithe Meal and the Corinthian Lord$1 (Bs Suppers - Gossai, Hemchand; Gossai, Hemchand; Rhodes, Michael (Peter Lang, 2022)
The Bible is filled with commands to care for the poor. But how does Scripture envision the people of God becoming a community capable of following those commands? In Formative Feasting, Dr. Michael J. Rhodes argues that meals stand at the heart of Scripture$1 (Bs strategy for moral formation oriented towards justice and solidarity. To make this case, Rhodes brings together a constructive, theological account of moral formation through practice with rigorous exegesis of the Deuteronomic tithe-meal and Corinthian Lord$1 (Bs Supper. By drawing on virtue ethics, ritual studies, and socio-economic research on meals in the ancient Near East and Greco-Roman world, Rhodes both demonstrates that these meals intended to transform the individual and corporate character of the communities that practiced them, and uncovers the "mechanics" of moral formation embedded within them. The result is a book that models a partnership between theological ethics and theological interpretation that overcomes the oft-lamented gap between exegesis and ethics, with important implications for contemporary communities of faith. Formative Feasting will be of special interest to researchers, students, and church leaders interested in moral formation and the Bible, as well as those interested in feasting and eating in Scripture. Seminary and college courses focused on issues of food in the biblical world, as well as those exploring the relationship between exegesis and ethics, will find Formative Feasting an essential addition to course readings.s